Value-Based Payment Reform and the Medicare Access and CHIP Reauthorization Act (MACRA) of 2015: A Primer for Plastic Surgeons - Squitieri, Lee (Plast Reconstr Surg, 2017)
In 2015, the U.S. Congress passed the Medicare Access and CHIP (Children’s Health Insurance Program) Reauthorization Act (MACRA), which effectively repealed the Centers for Medicare and Medicaid Services (CMS) sustainable growth rate (SGR) formula and established the CMS Quality Payment Program (QPP). MACRA represents an unparalleled acceleration toward value-based payment models and a departure from traditional volume-driven fee-for-service reimbursement. The QPP includes two paths for provider participation: the merit-based incentive payment system (MIPS) and advanced alternative payment models (APMs). The MIPS pathway replaces existing quality reporting programs and adds several new measures to create a composite performance score for each provider (or provider group) that will be used to adjust reimbursed payment. The advanced APM pathway is available to providers who participate in qualifying APMs and is associated with an initial 5% payment incentive. The first performance period for MIPS opens January 1, 2017 and closes December 31, 2017 and is associated with payment adjustments in January 2019. CMS estimates that the majority of providers will begin participation in 2017 through the MIPS pathway, but aims to have 50% of payments tied to quality or value through APMs by 2018. In this article, we describe key components of MACRA to providers navigating through the QPP and discuss how plastic surgeons may optimize their performance in this new value-based payment program.